On Hydromagnetic Boundary Layer of Casson Fluid Over Porous Inclined Magnetized Surface With Radiation and Convective Boundary Conditions - Golbert, Aloliga; Seini, Ibrahim Yakubu; Musah, Rabiu (Communications in Mathematics and Applications, 2022)
The boundary layer of a non-Newtonian Casson fluid flow over inclined porous magnetized surfaces with radiation and convective boundary conditions have been considered. The effects of the magnetic field, thermal radiation, convection with temperature fields at the boundaries of the surface are considered. The governing models have been transformed to ordinary differential equations  imploying the similarity approach. The effects of surface magnetization along with bulk parameters on the flow are presented in tables. The thickness of the thermal boundary layer has been enhanced due to the induced magnetic field leading to considerable improvement in the rate of heat transfer. The induced magnetized surface showed a similar influence on the skin friction, Nusselt number, and the Sherwood number. The study, therefore, recommends the incorporation of magnetized surfaces in MHD flows for efficient flows control.
Keywords: Magnetized plate; Non-Newtonian Casson fluid; Convective boundary conditions; Internal heat generation